Awakening dignity : a guide to living a life of deep fulfillment - Rinpoche, Phakchok, 1981-; Wu, Sophie (Shu-Chin) (Shambhala, 2022)
"A Buddhist master's guide to cultivating dignity through meditation, in order to live a more meaningful and fulfilling life. The notion of dignity is crucial to questions of how best to live a meaningful and fulfilling life, particularly for people who feel self-doubt and low self-esteem as well as those who can feel trapped by their anxiety, dissatisfaction, or even success. In today's environment, this seems to include most people. So, how can we possess authentic and unshakeable dignity? This book offers a unique and fresh approach to this question by drawing from the Tibetan Buddhist wisdom tradition. According to Buddhism, dignity is an inherent quality of fundamental wholeness and completeness that we all naturally possess. This understanding is based on the idea that our true nature is pure and that our heart is noble. Phakchok Rinpoche shows how knowing that we are whole and complete already, and gaining trust and certainty in that understanding, counteracts the common feeling that we are not enough, that something is missing. Gaining unwavering trust in ourselves protects us from life's ups and downs. With genuine dignity, we are not riddled with uncertainty, anxiety, or self-doubt; rather, we are able to face any circumstance with confidence, clarity, and compassion. Through reflections, examples, and simple meditations, such as embracing adversity and practicing compassion, this guide provides all the tools necessary to fully embody our fundamental dignity"--